Portal Zgodovina Slovenije - SIstory in avtorske pravice - Šorn, Mojca (Prispevki za novejšo zgodovino, 2021)
In the contribution, the authors outline the history of copyright law and present the development and theoretical framework of copyright and related rights in Slovenia. They place a special emphasis on copyright law in the digital age, manifesting it on the History of Slovenia % SIstory portal as an example of good practice, as they are convinced that without (adhering to) copyrights, all the necessary incentives for further creation in both the analogue and digital worlds are not guaranteed
Keywords: avtorske pravice; portal Zgodovina Slovenije - SIstory; SIstory; Zakon o avtorski in sorodnih pravicah (ZASP); zgodovinopisje